Ukuran Perusahaan, Jenis Opini Audit, Ukuran KAP, Ukuran Dewan Komisaris, Dan Ukuran Komite Audit Serta Audit Delay Pada Industri Perbankan Yang Listing Di Bursa Efek Indonesia - Sri Ambarwati; Kartika Nirwana Putri (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2016)
The purpose of this research is to analyze impact of firm size, type of audit opinion, reputation of audit firm, board of commissioner’s size, and committee audit size either partially or simultaneously significant influence toward audit delay in Banking Industry that listed on Indonesian Stock Exchange. The research from 2011 until 2014. Sampling method that used is purposive judgement sampling method. Of the 41 companies that are trading at the Indonesian Stock Exchange from 2011 until 2014, there were 28 companies that meet the characteristics of the sample that have determined. Data used in this research is financial report from each firm that published in the website www.idx.co.id. Process of data analysis performed with the assumption classic, multiple regression analysis and hypothesis testing. The result in research show partially, firm size, reputation of audit firm, and board of commissioner’s size havesignificant toward audit delay. Where as type of audit opinion and committee audit size are not influence toward audit delay.